KAJIAN LEGENDA CANDI GEDONG SONGO SERTA PEMANFAATANNYA SEBAGAI BAHAN AJAR SASTRA LISAN BERMEDIA INTERAKTIF BAGI WARGA BINAAN BRSAMPK ANTASENA - Hana Amalia, - (2020)
Legend was born and famous in various regions in Indonesia, included in the district of Semarang, This district has a lot of potential, apart from industrial and tourism potential, there are also diversity of folk tales that reflect to the customs, traditions, as well as the philosophy of life of the local society. There are approximately nineteen stories of folklore that recorded, preserved, and booked in the district of Semarang, but not all of these stories are known to the surrounding of society. The Folklore books that published by the Government of the Semarang district have very limited functions, only for data archives, and do not reach the wider society. When we ask somebody in the district of Semarang regarding the information about the folk tales, mostly of them knew only the legend of Rawa Pening. There are those who know only little part of the story. This assume that the society in the district of Semarang have limited knowledge regarding folklore. Based on that background, the researchers is interested in studying the legend of Gedong Songo Temple as an effort to preserve the regional literature. The aims of this study are to describe the structures, creation process and inheritance, narrative context, functions and values that contained in the legend of Gedong Songo Temple. The method used in this research is the descriptive analysis with an ethnographic approach. The process of creation and inheritance is carried out vertically and horizontally with memory media. There are four functions of the legend of the Gedong Songo temple, are as follows aesthetic functions, ethical functions, pragmatic functions, and historical functions. The values contained in the legend of the Gedong Songo temple are moral, social, religious and cultural education because there are values and norms that can be learned and imitated by the community. The Utilization of the results of this research is used as interactive multimedia teaching materials. Keywords: Oral Folklore, Legend, Interactive Multimedia Oral Literature Teaching Materials